COVID-19 pandemic and the impact on dental education: discussing current and future perspectives - Renato Assis MACHADO; Paulo Rogério Ferreti BONAN; Danyel Elias da Cruz PEREZ; Hercílio MARTELLI JÚNIOR (Sociedade Brasileira de Pesquisa Odontológica, 2020)
Abstract Due to the COVID-19 pandemic crisis, many dental schools and instructors are rethinking the way they teach and interact with students. New perspectives regarding a change in face-to-face activities, social isolation and the reformulation of clinical activities result in a transition toward e-learning and e-teaching processes. In this review, we discuss some favorable aspects and difficulties associated with virtual teaching and learning, searching for available tools and techniques as well as new perspectives.